Farmakološka in nefarmakološka terapija za zdravljenje primarne dismenoreje - Kavšak, Aleksandra (Obzornik zdravstvene nege, 2018)
Introduction: The article is based on a systematic review of the literature and identifies the different forms of pharmacological and non-pharmacological treatments which can help women with primary dysmenorrhea to reduce pain intensities. The aim of the study was to determine the forms of pharmacological and nonpharmacological therapy for the reduction of pain in primary dysmenorrhea through literature review. Methods: The databases that were searched included CINAHL, Medline, ScienceDirect and Cochrane Library. The following search terms were used: primary dysmenorrhea, menstrual pain, pharmacological intervention and non-pharmacological intervention. The search was limited to full text available in English language, published between 2007 and 2017 peer reviewed publications. The search yielded 571 results, but the final review included 13 studies. Results: 13 studies were reviewed, 5 of which were about pharmacological treatments and 8 of nonpharmacological treatments. The results of the systematic review showed that non-steroidal anti-inflammatory drugs offer a significant reduction of pain in most women with primary dysmenorrhea. Findings suggest that all forms of non-pharmacological treatment are not recommended and do not help to reduce pain intensity in patients with primary dysmenorrhea. Discussion and conclusion: The results of a systematic review of literature have shown that pharmacological treatment is more effective in reducing pain intensity as the drug takes effect within one hour after taking it, but causes some side effects.: The article is based on a systematic review of the literature and identifies the different forms of pharmacological and non-pharmacological treatments which can help women with primary dysmenorrhea to reduce pain intensities. The aim of the study was to determine the forms of pharmacological and nonpharmacological therapy for the reduction of pain in primary dysmenorrhea through literature review.
Keywords: boleča menstruacija; combined therapy; kombinirana terapija; pain reduction; painful menstruation; zmanjšanje bolečine